'Identify' and 'lock in': molecular integration during synaptic target recognition. - Hoang, B.; Chiba, A. (Cellular and molecular life sciences. CMLS, 1999)
Synaptic target recognition is a complex molecular event. In a differentiating presynaptic terminal, relatively 'rare' molecules first detect the cell identity of the synaptic target. Subsequently, many 'common' molecules continue the process of synaptogenesis. We present a theoretical framework for understanding synaptic target recognition and discuss the features of its molecular components and their integration, drawing on the rapid progress made in recent studies.